Is Chinese Culture Dualist?: An Answer to Edward Slingerland from a Medical Philosophical Viewpoint - Pan, Dawei (Journal of the American Academy of Religion, 2017)
A recent challenge by Edward Slingerland to the conventional view of Chinese thought is that China is no exception to the recent cognitive science hypothesis that dualism is an innate cognitive universal. However, a close reexamination of Slingerland’s evidence shows that it is biased. Extensive evidence across philosophy and medicine suggests that a concept of degrees of substantiality rather than a distinct barrier between mind and body underlies both early Chinese afterlife beliefs and ideas about the xin-body relationship. In particular, medical accounts of the xin’s dual role as the organ of thought and a physical organ does not reject the division between mind and body. A dualist claim, however weak, cannot explain China’s traditional focus on the link between physicality and mentality, especially in medicine. The cognitive science-driven attempt to recast the conventional holist claim of Chinese thought is an overly hasty attempt to take refuge in science.